Squeezed correlations of strange particles-antiparticles - Padula, Sandra S. [UNESP]; Dudek, Danuce M. [UNESP]; Socolowski, O. (Iop Publishing Ltd, 2010)
Squeezed correlations of hadron-antihadron pairs are predicted to appear if their masses are modified in the hot and dense medium formed in high-energy heavy ion collisions. If discovered experimentally, they would be an unequivocal evidence of in-medium mass shift found by means of hadronic probes. We discuss a method proposed to search for this novel type of correlation, illustrating it by means of D(s)-mesons with in-medium shifted masses. These particles are expected to be more easily detected and identified in future upgrades at RHIC.